The One Environmental System: Did we get it right? - Musodza, William Junior Tashinga (My University, 2018)
The report discusses the recently enforced mining environmental management system the One Environment System, which was introduced to deal with issues such as duplication of environmental impact assessment processes, cross-departmental turf wars, and general inefficiencies of the permitting system in South Africa. It delves into the mechanics of the current regime, highlighting the unconstitutionality of provisions in the enabling legislation, considering the different spheres of government principle, the Bill of Rights and constitutionally enshrined principles of governance. The report discusses a similar environmental management system used in Australia and how South Africa can improve on the One Environment System to combat its inefficiencies.
William Junior Tashinga Musodza, 713744 Masters by Research Report,2018